Reliability, Validity, and Factorial Structure of the Farsi Version of the Paranoia Checklist With Iranian Students. (December 2018) - Amirpour, Leila; Dadfar, Mahboubeh; Heydari Charvadeh, Majid; Birashk, Behrooz
Paranoid thought is one of the most common symptoms in psychiatric disorders. The Paranoia Checklist is a brief screening and diagnostic tool for clinical and subclinical paranoia. It has been used in research, clinical, and non-clinical settings. The Paranoia Checklist has not had its validity examined in university settings in Iran. A cross-sectional study was conducted to investigate the validation of the Farsi version of Paranoia Checklist in a randomized cluster sample of 365 Iranian volunteer college students selected from the Payame Noor University of Mashhad in Iran. They completed the Paranoia Checklist, the General Paranoia Scale, and the Symptom Checklist 90 Revised (SCL-90-R). The mean score of the Paranoia Checklist was 35.50 ( SD = 7.21). The Cronbach's α for the Paranoia Checklist was .87, indicating high internal consistency. The Paranoia Checklist correlated .42 with the General Paranoia Scale, .38 with the SCL-90-R subscales of Anxiety (ANX), Hostility (HOS), and Paranoia Ideation (PAR), and .37 with the Interpersonal Sensitivity (INTS), denoting moderate construct and criterion-related validity. The results of the factor analysis of the Paranoia Checklist identified three factors associated with the paranoid thoughts. The Paranoia Checklist has a multidimensional structure, and adequate validity and reliability. It can be used in the non-clinical, clinical, and research settings to measure paranoia in Iran.